Prospects for Use of Heptral in Hemoblastoses - V. B. Larionova; E. G. Gorozhanskaya (Общая реаниматология)
Intensive therapy of blood cancer patients is a new area of hematology. Its birth is associated with advances in modern chemotherapy that provide hope for long-term remission or even complete cure of blood system tumorous diseases. Today «therapy of support» is an obligatory constituent of antitumor treatment programs. Effective supporting therapy enables a patient to go through severe, but potentially reversible disturbances of vital organs at all stages of therapy. This also applies in full to drug-induced hepatotoxicity that frequently leads to hepatic failure (HF). Hepatic medicinal damages of varying severity develop in 2—10% of inpatients. The pathogenetic mechanisms of hepatic damage are very diverse; however, they are all characterized by the cell damage accompanied by an inflammatory reaction, cytolysis, and evolving fibrosis. There may be this scenario of the development of a pathological process really with a different trigger at the start in viral hepatitis, hepatic toxic damage, autoimmune hepatitis, metabolic syndrome, and other forms of acute and chronic liver damage. At the same time a hepatocyte, the principal hepatic parenchymal cell, is likely to be the focus of organ pathology. There are good grounds to believe that heptral (S-ademethionine) the metabolism of which has been well studied may be indicated and effective not only in oncohematology, but also in the programs of supporting therapy of intensive care units. In spite of many years’ clinical experience and numerous researches, the scope of its use has not been defined so far. Heptral’s abilities await in-depth experimental and clinical studies and the development and introduction of methods for the prevention and treatment of drug-induced hepatotoxicity are an important sociomedical problem of not only oncology, but also reanimatology, the solution of which will be able to increase the quality of life during treatment and rehabilitation. Key words: hemoblas-toses, supporting therapy, hepatotoxicity, heptral.